Physical Fitness Status Among Female Reserve Officers Training Unit (ROTU).-The Pre-test. - Kassim, Mohar; Othman, Norfazilawati; Rustam, Shahrulfadly; Ujang, Edawaty (International Journal of Engineering and Technology, 2018)
The ROTU cadets are trained to become an officer who are always ready to defence and resilience the country from all threats. The fitness level of each female ROTU cadets can be measured more systematically and accurately by implementing the test batteries. The objective of this study is to measure the fitness level among the female ROTU cadets based on the seven test, secondly to produce the Fitness Training Manual for the female ROTU cadet and thirdly to build the physical norms based on the seven test battery among the female ROTU cadets in UPNM. The whole research will involve 3 phases, pre-test for basic data collection, (4 weeks), intervention (12 weeks) and post data collection (4 weeks). From the purposive sampling, 212 female ROTU cadets were selected as the sample of the study. The instruments for pre-data collection involved the 7 test batteries (2.4 km running, sit-up, push up, 30-meter sprint, 10-meter zigzag, sit and reach and stand long jump) and self-administered questionnaire for demographic characteristics. The results of the pre-test came out with the seven physical fitness norms among female PALAPES cadet based on their age (19, 20 & 21). In conclusion, this physical fitness norm helps in the classification of physical fitness among the female ROTU cadets in UPNM. In average, the pretest showed not more than than 30% of them have an excellent physical fitness. The results of this study and the Fitness Training Manual can be used as a reference for future scientific studies especially among ROTU cadets in Malaysia.Keywords: Norms, Physical fitness, test batteries, female, ROTU.